Measuring activities in tobacco control across the EU. The MAToC - John Ulrich; Thyrian Jochen (BMC, 2006)
Abstract Background Objectives of this study are (a) to develop a comprehensive and economic tool to estimate tobacco control (TC) activities in single EU member states, (b) to compare TC activities between member states of the EU. This article provides the questionnaire and gives a benchmark of EU member states according to their perceived TC activities. Methods: An international workshop was specifically initiated to develop the questionnaire "Measuring Activities in Tobacco Control (MATOC)". TC experts from 8 European countries participated and chose 40 items to cover 11 general topics of TC. At the World Conference of Tobacco or Health in Helsinki 2003 participants were asked to fill out the questionnaire. N = 142 participants from EU-member states returned questionnaires. Results Subjects from the tobacco field in Finland gave the highest TC values to their country, followed by Sweden, Ireland, the UK and the Netherlands. The least active countries in TC were Greece and Germany, behind Austria, Spain, Belgium and Portugal. Italy, France and Denmark constituted the middle field. Conclusion The MATOC provides a profile of TC across European countries and delivers results that are plausible and fit into the existing findings. The data presented here fulfils the purpose to illustrate what is possible with the MATOC and underlines the value of such an approach in delivering information for policy makers and TC advocates how TC is perceived in each country. Yet, further validity testing is necessary, the number of experts per country differs and is partly rather small. Further research with the MATOC should encounter these limitations. The procedure though could serve as model of practice for alcohol and legal drug policy as well.